Biosurfactant Production from Pseudomonas aeruginosa ATCC27853 with Carbon Source from Crude Palm Oil for Oil Recovery - Amraini, Said Zul; Muria, Sri Rezeki; Bahruddin, Bahruddin; HS, Irdoni; Artha, Ulfa Dwi; Susanto, Reno (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Biosurfactants are surfactants that are synthesized by microorganisms using organic materials and have biodegradable properties, making them environmentally friendly. One of the applications of biosurfactants in the recovery of petroleum. This study aims to determine the type of biosurfactant produced by Pseudomonas aeruginosa bacteria using crude palm oil as the main carbon source, to determine the effect of variations in pH and CPO concentration on surface tension reduction and emulsification, and compare the best biosurfactant with surfactant synthesis. The production of biosurfactants has 3 stages, namely the bacterial preparation, the biosurfactant production, and the analysis in the form of surface tension, emulsification, crude oil removal, and FTIR. The best biosurfactant was obtained at pH 7 and a carbon source concentration of 3% v/v with surface tension and emulsification values ​​of 42.49 mN/m and 58%, respectively. The pH value and CPO concentration can affect the growth in the biosurfactant production process, thus also affecting the surface tension and emulsification values. The biosurfactants obtained were rhamnolipid biosurfactants. The biosurfactants produced in this study have lower crude oil recovery capabilities than synthetic surfactants with crude oil removal values ​​of 57.78% and 79.34%, respectively.